The development of the PlexiQoL: A patient‐reported outcome measure for adults with neurofibromatosis type 1‐associated plexiform neurofibromas. Issue 12 (21st October 2020) - Heaney, Alice; Wilburn, Jeanette; Rouse, Matthew; Langmead, Shannon; Blakeley, Jaishri O.; Huson, Susan; McKenna, Stephen P.
ABSTRACT: Background: To develop and validate a patient‐reported outcome (PRO) measure of quality of life (QoL), specific to patients with Neurofibromatosis Type 1 (NF1)‐associated plexiform neurofibromas (pNFs), suitable for use in clinical efficacy trials. The study was conducted in parallel in the UK and US. Methods: Qualitative interviews were conducted with patients to generate questionnaire content. Face and content validity of the draft scale was assessed by cognitive debriefing interviews (CDIs). A postal validation survey was conducted to identify the final version of the questionnaire (the PlexiQoL), establish its unidimensionality, and assess its psychometric properties. Results: Thematic analysis was performed on 42 interview transcripts. Thirty‐one CDIs revealed that patients found the draft scale to be comprehensible, relevant, and easy to complete. The postal validation survey was completed by 273 patients. Rasch analysis identified an 18‐item unidimensional scale that showed excellent internal consistency, reproducibility, and sensitivity to differences in patient‐perceived pNF severity, general health, and the use of pain medication. Conclusions: The PlexiQoL is the first disease‐specific PRO assessing the ability of adults with NF‐1 associated pNFs to meet their basic human needs. Clinical trials are planned to assess the sensitivity to change of the PlexiQoL in people undergoing treatment for pNFs. Abstract : The aim of this study was to develop and validate a patient‐reported outcome (PRO) measure of quality of life (QoL), specific to patients with Neurofibromatosis Type 1 (NF1)‐associated plexiform neurofibromas (pNFs), suitable for use in clinical efficacy trials. Rasch analysis identified an 18‐item unidimensional scale that showed excellent internal consistency, reproducibility and sensitivity to differences in patient‐perceived pNF severity, general health and the use of pain medication.